The Generation Game: Has Modern Contemporary Total Ankle Replacement (TAR) Improved Survivorship?. Issue 1 (January 2022) - Ahluwalia, Raju S.; St Mart, Jean-Pierre; Goh, En Lin; Hay, Daniel; Pilkington, Isobel; Bednarczuk, Nadja
Category: Ankle Introduction/Purpose: Total ankle replacements (TARs) provide pain relief with preservation of movement and function. The most successful TARs are either 2nd or current 3rd generation in design, whilst 4th generation implants are steadily being introduced. This meta-analysis evaluates the survivorship of 2nd, 3rd and 4th generation ankle replacements used today to determine whether any difference between generations and bearing types exist. Methods: A systematic review and meta-analysis of published data from January 2000 to January 2020 was conducted following PRISMA guidelines. Inclusion criteria: English language papers, adult population, >= 20 ankles with a minimum follow up >= 24 months, pre- and post-operative functional scores available. Clinical outcomes of primary TARs were evaluated as well as their associated survivorship. Statistical analyses were undertaken to determine survivorship and complications associated with the second, third and fourth generation implants and the bearing design. Ankle generations were determined from the original studies and confirmed based on literature set definitions. The modified Coleman Methodology Score was used to evaluate the quality of studies. Results: A total of 4642 TARs in 4487patients from 51-studies were included. The mean age was 61.9years and mean follow up of 57.8months. The most common indications were post-traumatic-OA (54.5%), primary-OA (25.5%) and inflammatory-arthropathy (15.2%). Relative-risk calculations showed significant reductions in nerve-injury (p < 0.01), post-operative fracture ( p < 0.01), wound complications (p < 0.01), radiolucencies ( p < 0.01), or heterotopic bone formation (p < 0.01), aseptic loosening (p < 0.01) for later generations. Sensitivity analysis performed for the withdrawal of 2 prostheses showed 2yr survivorship for 2nd, 3rd and 4th generation TARs was 95.3%, 97.9% and 98.9% (p < 0.05). Third-generation TARs had better 10-yr survivorship compared to 2nd generation (83.50% vs. 70.76%) (p < 0.01). Bearing design had little influence on survivorship. Conclusion: In the real world subsequent generations of modern contemporary TAR demonstrate lower rates of complications and improved survivorship independent of bearing design, without reaching designer series levels. Population changes have meant a reduction in mean age at implementation and the commonest pathology for a TAR has become post traumatic OA without a observed detrimental affect in outcomes. Even so, superior short-term survivorship of fourth generation implants is promising for the future of modern TAR surgery.